Hygiene, Sociality, and Culture in Contemporary Rural China : The Uncanny New Village - Lai, Lili (Book collections on Project MUSE., 2016)
This book presents a new perspective on attempts by the contemporary Chinese government to transform the diverse conditions found in countless rural villages into what the state's social welfare program deems "socialist new villages." Lili Lai argues that an ethnographic focus on the specifics of village life can help destabilize China's persistent rural-urban divide and help contribute to more effective welfare intervention to improve health and hygienic conditions of village life.